Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find all integer solutions of the following equation: $$x^4+x^3+x^2+x=y^2$$

share|cite|improve this question
Can you factor the left hand side? – Jyrki Lahtonen Jan 2 '14 at 10:58
y is even, and x is either odd, or a multiple of $4$. – Lucian Jan 2 '14 at 12:09
up vote 10 down vote accepted

When $|x|>1$ we have $$(2x^2+x)^2<4(x+x^2+x^3+x^4)<(2x^2+x+1)^2.$$

share|cite|improve this answer
+1 what a simple and beautiful argument! – achille hui Jan 4 '14 at 0:12
@achillehui Thank you, but I can't take credit. I learned this trick from Ed Burger's book The Number Jungle. – Byron Schmuland Jan 4 '14 at 0:21
+1 Learned a new trick today! May I ask if these types of techniques have a name? =D – Yong Hao Ng Jan 4 '14 at 1:14
@YongHaoNg I don't know if it has a special name. I suppose it only works on very special Diophantine equations, but it is certainly worth knowing! – Byron Schmuland Jan 4 '14 at 1:46
I see, I was wondering if the book has a name for it. Thanks~ =D – Yong Hao Ng Jan 4 '14 at 1:49

The equation

$$y^2 = x^4 + x^3 + x^2 + x = x(x+1)(x^2+1)\tag{*1}$$

has four trivial solutions over $\mathbb{Z}\times\mathbb{Z}$:

$$(x,y) = (-1,0), (0, 0),(1,\pm 2)$$

To determine whether there are other non-trivial solutions, let's look at an equivalent problem:

$$y^2 = \begin{cases} z(z + 1)(z^2 + 1), &\text{ for } z = x \ge 2\\ z(z - 1)(z^2 + 1), &\text{ for } z = -x \ge 2\tag{*2} \end{cases}$$

Notice $$\gcd(z(z\pm 1),z^2+1) = \gcd( \pm z - 1, z^2 + 1) = \gcd(\pm z - 1,2) = 1 \text{ or } 2$$

Any solution of $(*2)$ must have one of the following two factorizations:

$$\begin{cases} z(z\pm 1) &= p^2,\\ z^2 + 1 &= q^2,\\ y &= \pm pq;\end{cases} \quad\text{ or }\quad \begin{cases} z(z\pm 1) &= 2p^2,\\ z^2 + 1 &= 2q^2,\\ y &= \pm 2pq.\end{cases}\quad\text{ with } \gcd(p,q) = 1.$$

We can rule out the factorization on the left because for $z \ge 2$, $z^2 + 1$ is never a square. For the factorization on the right, we can rewrite the $x$ part as

$$\left\{\begin{array}{ccrl} (2 z \pm 1 )^2 &-& 8p^2 &= 1\\ z^2 &-& 2q^2 &= -1 \end{array}\right.\tag{*3}$$

Define $A, B : \mathbb{Z} \to \mathbb{Z}$ by

$$A(k) + B(k) \sqrt{2} = (1+\sqrt{2})^k$$

It is known the positive integer solutions of Diophantine equations like those in $(*3)$ has the form

$$\left\{\begin{array}{ccl} 2 z\pm 1 &=& A(2m)\\ 2p &=& B(2m)\\ z &=& A(2n-1)\\ q &=& B(2n-1)\\ \end{array}\right. \quad\quad\text{ for } m , n \in \mathbb{Z}_{+}. $$ It is clear $2 z \pm 1 \ge z \implies 2m \ge 2n-1$. Notice $\frac{A(k+1)}{A(k)} \to 1+\sqrt{2} > 2$ as $k \to \infty$. For any $n$ large enough such that $A(2n) > 2 A(2n-1) + 1$, there are no way to find a $m$ to satisfy $(*3)$. A brute force computation shows that this happens as early as $n \ge 2$.

This leaves us the cases $n = 1$. It is easy to check for $n = 1$, one can choose $m = 1$ to make $(*3)$ works. However,

$$ m = n = 1 \quad\implies\quad \left\{\begin{array}{ccl} 2 z\pm 1 &=& A(2) = 3 \\ 2p &=& B(2) = 2\\ z &=& A(1) = 1\\ q &=& B(1) = 1\\ \end{array}\right. \quad\iff\quad (x,y) = (1,\pm 2) $$ corresponds to a pair of trivial solutions we have covered before. The conclusion is aside from the four trivial solutions, $(*1)$ doesn't have any non-trivial solution.

share|cite|improve this answer

The following shows that the only solutions are $$(0,0),(-1,0),(1,2),(1,-2)$$ by using a birational transformation to an Elliptic curve.

1. Birational transformation to an Elliptic curve

Denote $$C: v^2-u^4-u^3-u^2-u=0$$ It is clear that if $u=0$, then $v=0$. For the other case, $u\neq 0$, we can divide by $u^4$: $$\dfrac{v^2}{u^4}-1-\dfrac{1}{u}-\dfrac{1}{u^2}-\dfrac{1}{u^3}=0$$ Rearranging: $$\left(\dfrac{v}{u^2}\right)^2=\left(\dfrac{1}{u}\right)^3+\left(\dfrac{1}{u}\right)^2+\left(\dfrac{1}{u}\right)+1$$ Which is in fact an Elliptic curve: $$E: Y^2=X^3+X^2+X+1$$ In other words, we have a birational transformation $\phi$: \begin{align*} \phi: C &\to E\\ (u,v) &\mapsto \left(\dfrac{1}{u},\dfrac{v}{u^2}\right) = (x,y) \end{align*} (We know this type of transformation exists since we can compute genus of $C$ to be 1.)

If $(u,v)\in \Bbb Z^2$ is an integer solution for $C$, then $\left(\dfrac{1}{u},\dfrac{v}{u^2}\right)$ is a rational point on $E$.

In other words, it suffices to find all rational points of the form $\left(\dfrac{1}{u},\dfrac{v}{u^2}\right)$ on $E$.

In particular, notice that $\dfrac{1}{u}$ has numerator $1$ which is very restrictive. We shall make use of this constraint to make our main deduction.

2. Rational points on $E$

Using Sage, we find that the Mordell-Weil group over $\Bbb Q$ has the structure $$E(\Bbb Q)\cong \Bbb Z_2\times \Bbb Z$$ Where the order two torsion is $P=(-1,0)$ and the free group generator is $Q=(0,1)$.
In other words all rational points are written as: $$E(\Bbb Q)=[a]P\oplus [b]Q, \;\;\;\; (a,b)\in [0,1]\times \Bbb Z$$

Clearly $Q$ does not correspond to a solution. On the other hand, $P=(-1,0)$ has $x$-numerator 1. Hence we let $u=-1$: $$v^2=(-1)^4+(-1)^3+(-1)^2+(-1)=0,$$ and we find a solution in $C$: $$(u,v)=(-1,0)$$

3. A useful lemma

We shall be using this later:

If $(X,Y)\in E(\Bbb Q)$, then: $$(X,Y)=\left(\dfrac{m}{e^2},\dfrac{n}{e^3}\right)$$ for some $$m,n,e\in \Bbb Z,\;\;\;\;\gcd(m,e)=\gcd(n,e)=1$$ (This can be shown using $p$-adic valuations.)

4. Solving the main problem

We have seen that $Q=(0,1)$ does not correspond to a solution. Similarly, $$[2]Q=\left(\dfrac{-3}{4}, \dfrac{-5}{8}\right)$$ so that $[2]Q$ also does not correspond to a solution.

Now let $R=P$ or $R=[a]Q, a\geq 2$. We want to show that $R\oplus Q$ cannot correspond to a solution. Then by induction $$\{P\oplus [a]Q,[a]Q\;|\;a\geq 1\}$$ cannot be a solution and we would have covered $[r]P\oplus [s]Q, (r,s)\in [0,1]\times \Bbb N$.

Since $R\neq Q$, we can derive a formula for point addition with $Q$: $$R\oplus Q=\left(\dfrac{2+x-2y}{x^2},\dfrac{4 + 3 x + 2 x^2 + x^3 - 4 y - x y}{x^3}\right)$$

Recall that if indeed some $(u,v)$ maps to a rational point in $E$, then the $x$-coordinate satisfies: $$x(R\oplus Q)=\dfrac{2+x-2y}{x^2}=\dfrac{1}{u}$$ Now using our lemma in (3): $$\dfrac{2+x-2y}{x^2}=\dfrac{2+(m/e^2)-2(n/e^3)}{(m/e^2)^2}=\dfrac{1}{u}$$ $$\dfrac{(2e^3+me-2n)e}{m^2}=\dfrac{1}{u}$$ From which we draw the conclusion that $$e|m^2$$ Since $\gcd(m,e)=1$, this can only happen if $e=\pm 1$. Either way, this implies that $(x,y)=(m/e^2,n/e^3)$ are integral points.

(Perhaps can be solved without needing this information, but quite tedious.)

Sage tells us that the only integral points are $$(-1, 0), (0,\pm 1), (1,\pm 2), (7,\pm 20)$$ of which $(0,\pm 1)=\pm Q$ is not possible by construction of $R$.

Individual checking of the rest tells us that only $(-1,\pm 0),(1,\pm 2)$ results in $u=\pm 1$. We have seen the case $u=-1$ in section (2). For $u=1$:: $$v^2=1^4+1^3+1^2+1=4$$ From which we deduce $v=\pm 2$. Thus far we have the points $$(u,v)\in \{(0,0),(-1,0),(1,2),(1,-2)\}$$

From the induction, we conclude that there are no other possible candidates corresponding to \begin{align*} R &=P\oplus [a]Q, a\geq 1\\ R &= [a]Q, a\geq 1 \end{align*}

It remains to cover the rest of the cases. Since $P$ is order two, $[-1]P=P$. Then immediately $$P\oplus [a]Q = [-1]P\oplus [a]Q, a\geq 0$$ so that these are also not solutions.

The inverse of a point does not change the $x$-coordinates: $$-(x,y)=(x,-y)$$ Therefore if $R$ is not a solution, then $-R$ is also not a solution. This shows that $$-(P\oplus [a]Q)=[-1]P\oplus [-a]Q=P\oplus [-a]Q$$ $$-([a]Q)=[-a]Q, a\geq 1$$ are not solutions.

Therefore we have covered all the cases and we are done.

5. Sage codes for reference

E = EllipticCurve([0,1,0,1,1]);
tor = E.torsion_points();
rank = E.rank();
gens = E.gens();
integralPoints = E.integral_points();

share|cite|improve this answer

EDIT : The case (1) in my answer has a big mistake. The case (2) is true.

$(x,y)=(0,0)$ is one of the solutions. In the following, suppose that $(x,y)\not=(0,0).$

We have $$x(x+1)(x^2+1)=y^2.$$ First, we know that $x$ and $x+1$ are coprime, and that $x$ and $x^2+1$ are coprime, too. This leads that there is an integer $k$ such that $x=k^2.$ (see the right hand side)

In the following, we break up the answer into two cases.

(1) The case that $x+1$ and $x^2+1$ are not coprime.

Letting $$x+1=ps,x^2+1=pt\ \ (\text{$p$ is a prime number, $s,t\in\mathbb Z$})$$ we have $$(ps-1)^2+1=pt\iff p(t-ps^2+2s)=2\Rightarrow p=2.$$ So, we know we only have the following possibilities : $$x+1=0,\pm1, \pm2^k\Rightarrow x=-1,0,-2,-1\pm2^k.$$ However, we have $x\not=-1, x\not=0, x\not=-2$, because $x$ has to be a square of an integer (and $x\not=0$). So, we have $$x=-1\pm2^k.$$ In the same argument, we have $$x^2=-1\pm2^l.$$ Note that $k,l\ge1\in\mathbb Z.$

Hence, we have $$(-1\pm2^k)^2=-1\pm2^l\iff 2^{2k}\mp2^k+2=\pm2^l\iff 2^{2k-1}\mp2^{k-1}+1=\pm2^{l^1}.$$ Now, if $k-1\ge1$ and $l-1\ge1$, then we know that the left hand side is odd, and the right hand side is even, which is a contradiction.

So, we have "$k=1$ or $l=1$".

This leads $x=\pm2^k-1=\pm2^1-1\Rightarrow x=1,-3\Rightarrow x=1.$ ($x^2$ has to be a square.) Also, this leads $x^2=\pm2^l-1=\pm2^l-1\Rightarrow x^2=1,-3\Rightarrow x=1.$

So, this case leads $(x,y)=(1,\pm 2).$

(2) The case that $x+1$ and $x^2+1$ are coprime.

In this case, we know any two of $x,x+1,x^2+1$ are coprime. So, this leads that each of $x, x+1,x^2+1$ has to be a square number of an integer. However, it is impossible that $x$ and $x+1$ are both square numbers except $x=0$. However, we suppose that $x\not=0$ at the top. Hence, this case has no solution.

Now we reach a conclusion that the solutions of the given equation is only the followings:


share|cite|improve this answer
How did you go from $\gcd(x+1,x^2+1)=2$ to the conclusion that $x=\pm 2^k$? Agree with your case 2. – Jyrki Lahtonen Jan 2 '14 at 12:16
@i totally agree with @Jyrki this is a big "jump" – Konstantinos Gaitanas Jan 2 '14 at 12:19
Oh, you are right... I need to check it... but I'm tired:) I'll edit or delete this answer later. sorry. – mathlove Jan 2 '14 at 12:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.